Controlling wobec wybranych elementów zarządzania przedsięwzięciem - Klinowski, Marcin (Controlling Towards Some Elements of Project Management, 2005)
Project management is more and more often applied by companies nowadays. Beyond all doubt controlling plays the key role in this method. The foregoing paper presents the place that controlling takes in project management. The first part shows the presence of controlling instruments in individual stages of project execution. However, the second part describes working of different forms of project controlling in comparison to organization charts.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (2); 2005; nr 1059, s. 267-273